GROWTH OF BARU AND GONCALO-ALVES SEEDLINGS IN DEGRADED SOIL, SUPPLEMENTED WITH RESIDUE IN ILHA SOLTEIRA-SP STATE - Gonzaga da Silva Mizobata, Kellian Kenji [UNESP]; Rodrigues Cassiolato, Ana Maria [UNESP]; Maltoni, Katia Luciene [UNESP] (Centro Pesquisas Florestais, Ufsm, 2017)
The revegetation process represents an alternative to recovery of areas with exposed soil. The aim of this research was evaluate the growth of Dipteryx alata (baru) and Astronium fraxinifolium (goncalo-alves) seedlings in degraded soil, compacted and not, supplemented with agro-industrial residue, and verify the possibility of using this as a chemical soil conditioner. The experiment was conducted at UNESP/Ilha Solteira Campus, under protected cultivation, with the following treatments: 3 doses of residue (0, 15 and 30 t ha(-1)), two densities (1.0 and 1.5 g cm(-3)) and two indicator plants (Dipteryx alata e Astronium fraxinifolium). The selected plants are arboreal species from 'cerrado' biome, which occur in the vicinity of the degraded area, where the soil was collected. The seedlings were evaluated 7 months after roughing, for height, diameter of stem, number of leaves, fresh and dry weight of shoots and roots, and the soil was evaluated for fertility. The results show that the agro-industrial residue (RA) has increased the pH, potassium, calcium and magnesium, and reduced the exchangeable aluminum. The Dipteryx alata fresh root weight, was negatively influenced by compaction and showed little demanding for nutrients added by RA. Fresh root weight and height of Astronium fraxinifolium were negatively influenced by compaction whereas the addition of agro-industrial residue increased the plant height, stem diameter, fresh and dry weight of shoot and root. The root morphology was affected by compaction, in both species. The used substrate presents a high capacity of particles reorganization, resulting in a high density, without force application.
Keywords: Cerrado biome; Sugar-cane bagasse ash (SCBA); soil fertility